Standard Patterns of Considerations in Law, District Regulation and Qanun Based on Legal Rules in Indonesia - Husna Sartika; Eddy Purnama; Ilyas Ismail (Pancasila and Law Review, 2021)
The consequence of the state of the law is legislation to be an essential instrument in regulating public life. However, in some parts of Indonesia, they can make their regional regulation slightly different from the constitution, wherein this article will focus on Qanun in Aceh Province. The research used in this paper is normative law research. This research used sequential data or library data. Secondary data consists of primary law materials, secondary law materials, and tertiary law materials. The approach method used is the legislative approach and the conceptual approach. The formulation of the problem in this paper is how the standard pattern of consideration in the Law, Regional Regulations, and Qanun is based on legislation. The results show that in the Law in Consideration, Consider using the word "membentuk" or "form" because the law-making institution consists of legislative institutions and executive institutions. Regional regulation considers using the word "menetapkan" or "establish" because the institution that makes local regulations is a local government consisting of elements of local governments and local people's representative councils. This consideration follows Annex II of Law Number 12 of 2011 on the Establishment of Legislation as amended by Law Number 15 of 2019. However, the Qanun used the word "membentuk" or "form" due following Article 233 paragraph (1) of Law Number 11 the Year 2006 on Aceh Governance and Annex II of Aceh Qanun Number 5 of 2011 on the Procedures for the Establishment of Qanun.